Delayed diagnosis of glaucoma in Coffin-Siris syndrome - Angela C. Chen; Matthew Miller; Michael Kapamajian; Monica Khitri (American Journal of Ophthalmology Case Reports)
Purpose: To report a case of delayed diagnosis of glaucoma in a patient with Coffin-Siris Syndrome (CSS) who did not have any other predisposing risk factors or typical anterior segment signs of congenital glaucoma. Observations: A 27-year-old male with CSS was referred to the ophthalmology department for evaluation of strabismus. Past ocular history included a diagnosis of right morning glory anomaly and bilateral hyperopic astigmatism. Initial exam in the clinic was notable for visual acuity of 20/80 in the right eye and 20/40 in the left eye. Given difficulty with exam in the outpatient setting, the patient underwent exam under anesthesia. Intraocular pressures (IOPs) were 38 mmHg OD and 23 mmHg OS at induction and gonioscopy was significant for high iris insertion and prominent iris processes in both eyes. On dilated fundus exam, the right eye had a severely pallorous and cupped optic nerve; the left eye was also cupped but less so. Elevated IOPs and nerve cupping was consistent with a diagnosis of glaucoma. Conclusions and importance: Patients with CSS may develop glaucoma and should be screened for this important ophthalmic association, even in the absence of external signs of pediatric glaucoma including an enlarged cornea, anterior segment dysgenesis, or other risk factors for glaucoma such as steroid use.